Human-centred design bolsters vaccine confidence in the Philippines: results of a randomised controlled trial - Reñosa, Mark Donald; Wachinger, Jonas; Guevarra, Jerric Rhazel; Landicho-Guevarra, Jhoys; Aligato, Mila F.; Endoma, Vivienne; Landicho, Jeniffer; Bravo, Thea Andrea; Malacad, Carol; Demonteverde, Maria Paz; Silvestre, Catherine; Bärnighausen, Kate; et al. (BMJ global health, 2023)
Background The public’s confidence in vaccinations has eroded, and anti-vaccination movements have gained traction around the world, including in the Philippines. ‘Salubong’, a Filipino term, refers to welcoming someone back into one’s life and elicits ideas about friendship and family relationships. We extended this concept to vaccines in efforts to design an intervention that would re-welcome vaccines into homes. - Methods Using human-centred design, we developed and refined a story-based intervention that engages Filipino families, community leaders and community health workers. We conducted a randomised controlled trial among 719 caregivers of small children to test the developed intervention against a control video. We assessed the binary improvement (improvement vs no improvement) and the amount of improvement in vaccine attitudes and intentions after intervention exposure. - Results Although the intervention group began with marginally higher baseline vaccine attitude scores, we found that 62% of the intervention group improved their vaccine attitude scores versus 37% of the control group (Fisher’s exact, p<0.001). Among individuals whose scores improved after watching the assigned video, the intervention group saw higher mean attitude score improvements on the 5-point scale (Cohen’s d=0.32 with 95% CI 0.10 to 0.54, two-sided t-test, p<0.01). We observed similar patterns among participants who stated that they had previously delayed or refused a vaccine for their child: 67% of 74 in the intervention group improved their vaccine attitude scores versus 42% of 54 in the control group (Fisher’s exact, p<0.001). Among the subset of these individuals whose scores improved after watching the assigned video, the intervention group saw higher mean attitude score improvements on the 5-point scale that were marginally significant (Cohen’s d=0.35 with 95% CI −0.01 to 0.70, two-sided t-test, p=0.06). - Conclusions Our results provide solid evidence for the potential of co-designed vaccine confidence campaigns and regulations.
Gesehen am 07.12.2023